2022
DOI: 10.21315/aamj2022.27.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Enterprise Risk Management and Cost of Capital

Abstract: This paper investigates the effect of enterprise risk management (ERM) implementation on the cost of capital (cost of debt [Cd], cost of equity [Ce], and weighted average cost of capital [WACC]) for the oil and gas industry. The research is conducted using panel data analysis from 2008?2017 for 41 oil and gas companies publicly listed on the Bursa Malaysia. ERM implementation data is collected from company annual reports, while the cost of capital data is obtained from Thomson Reuters DataStream. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This study aims to confirm whether adequate risk management techniques provide reward systems to firms to reduce the cost of capital and reduce the sustainability risk to improve the industry's sustainable development (Shad et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to confirm whether adequate risk management techniques provide reward systems to firms to reduce the cost of capital and reduce the sustainability risk to improve the industry's sustainable development (Shad et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Applying regression as the estimation technique, the results showed that market risk management positively and significantly affects financial performance. Muhammad et al, (2022), studied the effect of ERM on the cost of capital which is considered a measure of financial performance given its effect on profitability. Measures of both independent and dependent variables were obtained from secondary sources; ERM was measured using S&P ERM scores while cost of equity and cost of debt were obtained from Thomson Reuters Datastream.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The convenience of BNPL, the flexibility in repayment terms, and the ease of accessing credit through this system can influence consumers to embrace and adopt this innovative payment method. DOI theory developed by Everett Rogers, explores how new ideas, innovations, or technologies spread and are adopted within a social system [15], [16]. This theory identifies five key elements that influence the rate of adoption: relative advantage (perceived benefits over existing alternatives), compatibility (fit with existing values and needs), complexity (ease of understanding and use), observability (visibility of results), and trialability (opportunity to experiment with the innovation).…”
Section: Theoretical Frameworkmentioning
confidence: 99%